Impact of Cigarette Smoking on Outcome of Hepatocellular Carcinoma after Surgery in Patients with Hepatitis B - Zhang, Xu-Feng (Public Library of Science, 2014)
BACKGROUND AND OBJECTIVES: Cigarette smoking is a potential risk factor for hepatocellular carcinoma (HCC) initiation, partially through interaction with hepatitis B virus (HBV). We examined the hypothesis that cigarette smoking might be associated with HBV-related HCC recurrence and patient survival after curative surgery. PATIENTS AND METHODS: Data of 302 patients with HBV infection who had undergone curative resection for HCC were prospectively collected from 2008 to 2011. Smoking status and smoking quantity (pack-years, PY) were asked at admission. Factors affecting recurrence-free survival (RFS) were examined. RFS and liver-specific mortality (LSM) stratified by risk factors were compared with log-rank test. RESULTS: 109 were current smokers. Current smokers were not different from non-smokers in tumor burden and surgical procedure. Univariate and multivariate analysis identified that heavy smoking (PY ≥20) was the most significant factor associated with HBV-related HCC recurrence after curative surgical resection (p = 0.001), followed by anti-HBV treatment (p<0.01), current smoking (p = 0.028), surgical margin <1 cm (p = 0.048) and blood transfusion >600 ml (p = 0.028). The median RFS in non-smokers, ex-smokers and current smokers was 34 months, 24 months and 26 months, respectively (p = 0.033). Current smokers had significantly worse RFS rate and increased 5-year cumulative LSM than non-smokers (p = 0.024, and p<0.001, respectively). Heavy smokers had significantly worse RFS than non- and light smokers (0<PY<20) (p<0.001, respectively) and higher cumulative LSM than non-smokers and light smokers (p = 0.003 and 0.001, respectively). Furthermore, in current smokers, continuing smoking postoperatively was strongly associated with poorer RFS and higher LSM than those who quit smoking postoperatively (p = 0.016 and p = 0.003, respectively). CONCLUSIONS: Smoking history and quantity appears to be risk factors for HBV-related HCC recurrence and LSM of patients after surgery. For smokers, continued smoking postoperatively might accelerate tumor recurrence and patient death. Therefore, smoking abstinence should be strongly recommended to patients pre- and postoperatively.